Instability of C154Y variant of aldo-keto reductase 1C3. (1st October 2017) - Endo, Satoshi; Takada, Sayaka; Honda, Ryo P.; Müller, Kathrin; Weishaupt, Jochen H.; Andersen, Peter M.; Ludolph, Albert C.; Kamatari, Yuji O.; Matsunaga, Toshiyuki; Kuwata, Kazuo; El-Kabbani, Ossama; Ikari, Akira
Abstract: Aldo-keto reductase (AKR) 1C3 is a cytosolic enzyme that metabolizes steroids, prostaglandins, toxic aldehydes and drugs. Recently, some nonsynonymous single nucleotide polymorphisms of AKR1C3 have been suggested to impact steroid and drug metabolism. In this study, we examined the effects of C154Y and L159V variants of AKR1C3 on stability and function of the enzyme. Both variants had been detected in patients with the neurodegenerative disease amyotrophic lateral sclerosis. Recombinant wild-type (WT), C154Y and L159V enzymes were similar in specific activity, but C154Y displayed much lower thermostability than WT and L159V. C154Y was inactivated by 10-min incubation at >25 °C, and about 90% of its activity was lost at 40 °C. Differential scanning fluorimetry revealed that T m (thermal denaturation midpoint) of C154Y was lower than that of WT. In order to study the cause of thermosensitivity of C154Y, we prepared C154F and C154S mutant AKR1C3s. Like C154Y, C154F was highly sensitive to thermal inactivation, whereas C154S showed almost the same thermostability as WT. The C154F and C154Y variants induced secondary and tertiary structural changes in AKR1C3 at 40 °C as reflected by their altered circular dichroism and 8-anilinonaphthalene-1-sulfonate fluorescence characteristics. These results suggest that the replacement of C154 with a residue possessing a bulky aromatic side-chain impairs the folding of the α-helix containing C154 and its neighboring secondary structures, leading to low thermostability of AKR1C3. AKR1C3 metabolizes cytotoxic 4-oxo-2-nonenal into a less toxic metabolite, and overexpression of WT in HEK293 cells alleviated the 4-oxo-2-nonenal-induced cytotoxicity. In contrast, the overexpression of C154Y in the cells did not show such a significant protective effect, suggesting that C154Y is unstable in cells. Highlights: Two AKR1C3 variants, C154Y and L159V, were identified in patients with familial ALS. Recombinant C154Y enzyme showed lower thermostability than WT and L159V enzymes. The C154Y enzyme was rapidly inactivated even at 37 °C. The inactivation resulted from altered α-helical structure by the C154Y mutation. The C154Y enzyme was suggested to exist as an inactive form in cells.